2018
DOI: 10.3390/min8080323
|View full text |Cite
|
Sign up to set email alerts
|

(10.4) Face of Ordered and Disordered Dolomite, MgCa(CO3)2: A Computational Study to Reveal the Growth Mechanism

Abstract: In this study, the stability of the (10.4) face of dolomite was systematically investigated. The surface energies at 0 K of the different (10.4) surfaces resulting from the cut of both ordered and disordered bulk structures were determined and compared, to establish how different atomic configurations (surface terminations) can affect the stability of the investigated face. To study the thermodynamic behavior of a surface, a 2D periodic slab model and the ab initio CRYSTAL code were adopted. The surface energi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…According to the terminology universally accepted concerning epitaxy, when the lattice constants of phases A and B match, that is when (1 × 1)-A ≡ (1 × 1)-B, the interface is said to be coherent; when a relation such as (m × n)-A ≡ (k × s)-B exists, with m, n, k and s integers (and the supercell parameters are not too long on the lattice length scale), the interface is commensurate; otherwise it is incommensurate. Moreover, as widely discussed in some recent papers, [2][3][4][5][6][7][8][9] crystal faces (hkl) A and (h′k′l′) B can show several surface terminations (e.g., different structures for the same surface). If the number of the surface terminations is p and r for (hkl) A and (h′k′l′) B , respectively, the number of possible interface configurations can be very high, p × r.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…According to the terminology universally accepted concerning epitaxy, when the lattice constants of phases A and B match, that is when (1 × 1)-A ≡ (1 × 1)-B, the interface is said to be coherent; when a relation such as (m × n)-A ≡ (k × s)-B exists, with m, n, k and s integers (and the supercell parameters are not too long on the lattice length scale), the interface is commensurate; otherwise it is incommensurate. Moreover, as widely discussed in some recent papers, [2][3][4][5][6][7][8][9] crystal faces (hkl) A and (h′k′l′) B can show several surface terminations (e.g., different structures for the same surface). If the number of the surface terminations is p and r for (hkl) A and (h′k′l′) B , respectively, the number of possible interface configurations can be very high, p × r.…”
Section: Introductionmentioning
confidence: 83%
“…By examining Table 1, it is possible to highlight that: 2 than the surface energy of (10.4) Cc , γ (10.4) Cc being 0.507 J m −2 ; 2 (ii) 7 than the surface energy of (00.1) Cc , where γ (00.1) Cc = 0.711 J m −2 ; 7 (iii) (001) Ar shows a strong affinity with (1 ¯01) Za ; indeed, the (001) Ar /(1 ¯01) Za interface has an interfacial energy of…”
Section: (I) Habit Modification Of Calcitementioning
confidence: 99%
“…5−7 In particular, recent quantum mechanical and empirical calculations on dolomite nucleation and growth provided new insights into the formation of ordered dolomite. 8,9 These calculations have shown that while a dolomite bulk structure with a completely ordered cation arrangement is the configuration that is energetically most favorable, the dolomite (10.4) surface is energetically more favorable when Ca 2+ and Mg 2+ cations are randomly distributed, i.e., when such a surface shows cation disorder. 8,9 According to Bruno et al, 9 the cationic order in the dolomite bulk structure would increase progressively by the intracrystalline diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, cation ordering arrangements in minerals have been studied using atomic computational methods. In particular, recent quantum mechanical and empirical calculations on dolomite nucleation and growth provided new insights into the formation of ordered dolomite. , These calculations have shown that while a dolomite bulk structure with a completely ordered cation arrangement is the configuration that is energetically most favorable, the dolomite (10.4) surface is energetically more favorable when Ca 2+ and Mg 2+ cations are randomly distributed, i.e., when such a surface shows cation disorder. , According to Bruno et al, the cationic order in the dolomite bulk structure would increase progressively by the intracrystalline diffusion process. The sluggishness of such a process at ambient conditions is consistent with dolomite formation times of millions of years.…”
Section: Introductionmentioning
confidence: 99%
“…All values are expressed in erg cm −2 . γ Cal10.4 and γ Zab 001 were calculated at B3LYP level by Bruno and Bittarello49 and Bruno and Prencipe,50 respectively.…”
mentioning
confidence: 99%